2022
DOI: 10.1007/s10147-022-02134-8
|View full text |Cite
|
Sign up to set email alerts
|

Utility of whole exome sequencing analysis in differentiating intrapulmonary metastatic multiple ground-glass nodules (GGNs) from multiple primary GGNs

Abstract: Purpose Clinical evidence of metastasis with ground-glass nodules (GGNs) has been reported, including pulmonary metastasis and distant metastasis. However, the clonal relationships of multiple GGNs at the genetic level remain unclear. Experimental design Sixty tissue specimens were obtained from 19 patients with multiple GGN lung cancer who underwent surgery in 2019. Whole exome sequencing (WES) was performed on tissue samples, and genomic profiling and cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
(41 reference statements)
0
5
0
Order By: Relevance
“… aCGH for CNVs Girard [2009] 42 Arai [2012] 43 Liu [2016] 44 Sun [2018] 26 Vincenten [2019] 45 Noise: 8% (2/24 pairs); Equivocal calculation: 18% (4/22 pairs) 0% 33% (2/6) 0% 17% (7/41 pairs) 22% (4/18 pairs) 17% (2/12) 25% (1/4) 35% (7/20 pairs) 38% (13/34 pairs) Acceptable accuracy of discrimination; Wide detection range. Low throughput WES for CNVs Zhou [2022] 46 63% (12/19) NA Acceptable accuracy of discrimination; High throughput; Wide detection range. Mate-pair NGS for rearrangements Murphy [2014] 47 Murphy [2019] 48 0% 0% 27% (3/11) 24% (9/37) Complex bioinformatic analysis MicroRNA qRT-PCR for 5 miRNAs Zhou [2016] 49 0% 25% (6/24) Simple operation; Help reveal the post-transcriptional regulation in MLCs Unproven accuracy Dynamic change of miRNA and overlap between individuals doubt the reliability.…”
Section: Genomics-based Methods For Discriminating Mlcsmentioning
confidence: 99%
See 1 more Smart Citation
“… aCGH for CNVs Girard [2009] 42 Arai [2012] 43 Liu [2016] 44 Sun [2018] 26 Vincenten [2019] 45 Noise: 8% (2/24 pairs); Equivocal calculation: 18% (4/22 pairs) 0% 33% (2/6) 0% 17% (7/41 pairs) 22% (4/18 pairs) 17% (2/12) 25% (1/4) 35% (7/20 pairs) 38% (13/34 pairs) Acceptable accuracy of discrimination; Wide detection range. Low throughput WES for CNVs Zhou [2022] 46 63% (12/19) NA Acceptable accuracy of discrimination; High throughput; Wide detection range. Mate-pair NGS for rearrangements Murphy [2014] 47 Murphy [2019] 48 0% 0% 27% (3/11) 24% (9/37) Complex bioinformatic analysis MicroRNA qRT-PCR for 5 miRNAs Zhou [2016] 49 0% 25% (6/24) Simple operation; Help reveal the post-transcriptional regulation in MLCs Unproven accuracy Dynamic change of miRNA and overlap between individuals doubt the reliability.…”
Section: Genomics-based Methods For Discriminating Mlcsmentioning
confidence: 99%
“…In most circumstance, they are considered as MPLCs, 7 however, differential diagnosis is still in need since some appear to be IPMs based on genomic profiles. 46 , 70 , 71 , 89 , 90 Moreover, patients with multiple GGNs have been found to exhibit no-response to PD-1 inhibitors, negative PD-L1 expression, downregulation of HLA-related genes, and defective T-cell functions. 91 In these patients, testing negative or low-level TME markers would hardly benefit the differential diagnosis.…”
Section: Potential Molecule-based Methods For Discriminating Mlcsmentioning
confidence: 99%
“…Clinical decisions regarding the treatment of SM-GGNs are complicated by the difficulty in distinguishing synchronous multiple primary lung cancers from intrapulmonary metastases. According to some studies, SM-GGNs may have a common origin, and intrapulmonary metastasis may occur even in the early stages of lung cancer ( 11 , 31 , 40 ). However, some studies have found that SM-GGNs mostly originate independently ( 28 , 33 ).…”
Section: Gene Mutations In Ggnsmentioning
confidence: 99%
“…Multiple ground glass nodules (GGNs) represent a distinct subtype of LUAD characterized by favorable prognosis, rare occurrence of metastases, and pathology diagnosis often falling into categories such as AIS, MIA, or LPA. Recent studies have demonstrated that most multiple GGNs are unrelated clones, 44,45 yet several studies identified explicit metastatic foci among GGNs, 46,47 even between AIS and AAH, 48 considering STAS. AIS or MIA are usually treated as separate tumors, 49 the impact of potential metastatic foci on prognosis remains underexplored, lacking sufficient evidence to prompt alterations in clinical decision-making.…”
Section: Diagnoses Of Mplc and Distinguishing From Ipmmentioning
confidence: 99%